(Invited) High-Speed Analog Resistance Change in TaOx Synthesized by Reactive Sputtering. (20th July 2018) - Shima, Hisashi; Takahashi, Makoto; Naitoh, Yasuhisa; Akinaga, Hiroyuki
Abstract : We successfully demonstrated the high-speed analog resistance change (ARC) in the TiN/TaO x -L/TaO x -H/TiN, where TaO x -L and TaO x -H respectively denote the tantalum oxide thin film having the lower and higher resistivity synthesized by the reactive sputtering process. Observed ARC is expected to be applicable to the nonvolatile weight value in the artificial perceptron and the human brain inspired information processing technology. The resistance change speed is as fast as 500 ns and much faster that the information transmission speed in the actual neuron cell.